PERTUMBUHAN JABON PUTIH DI AREAL PENELITIAN TANAM RUMPANG PT. SARMIENTO PARAKANTJA TIMBER (Jurnal ForestrIndo, 2024)
The Gap Planting and Gap Cutting (GPGC) silvicultural system is expected to be one of the silvicultural systems to rehabilitate degraded natural forests. This study aims to determine the growth of white jabon (Anthocephalus cadamba) planted in a gap and to determine the effect of field slope on the growth of white jabon. This research method used the census and measurement of the diameter and total height of the white jabon trees contained in 16 gaps with an area of 2000  each. The research results showed that the average diameter of the two-year-old white jabon trees was 7.42 cm and the average total height of the trees was 651.11 cm. Statistical tests showed that there were significant differences in the effect of field slopes on the white jabon growth. White Jabon grows better on steep slopes areas compared to flat and moderate slopes areas.